Displaced vestigial remembrance: a memory archive and architectural actants challenging the forgetfulness of war on the Bloemfontein concentration camp - Cantor, Keanan (University of the Free State, 2025)
The seething wounds inflicted by the South African War are continually suppressed by a pervasive state of historical amnesia transcending displacement during ongoing global conflicts. This suppression has induced memory to a mere psychological recollection, rendering society oblivious to the imperceptible nexus of displacement that interconnects humanity. Consequently, this research posits the following question: 𝘏𝘰𝘸 𝘤𝘢𝘯 𝘢 𝘸𝘦𝘣 𝘰𝘧 𝘥𝘪𝘴𝘳𝘶𝘱𝘵𝘦𝘥 𝘢𝘳𝘤𝘩𝘪𝘵𝘦𝘤𝘵𝘶𝘳𝘢𝘭 𝘢𝘤𝘵𝘢𝘯𝘵𝘴, 𝘴𝘪𝘵𝘦𝘥 𝘰𝘯 𝘵𝘩𝘦 𝘯𝘰𝘯-𝘱𝘭𝘢𝘤𝘦 𝘰𝘧 𝘵𝘩𝘦 𝘤𝘰𝘯𝘤𝘦𝘯𝘵𝘳𝘢𝘵𝘪𝘰𝘯 𝘤𝘢𝘮𝘱 𝘧𝘰𝘳𝘮𝘦𝘥 𝘪𝘯 𝘉𝘭𝘰𝘦𝘮𝘧𝘰𝘯𝘵𝘦𝘪𝘯 𝘥𝘶𝘳𝘪𝘯𝘨 𝘵𝘩𝘦 𝘚𝘰𝘶𝘵𝘩 𝘈𝘧𝘳𝘪𝘤𝘢𝘯 𝘞𝘢𝘳, 𝘢𝘨𝘪𝘵𝘢𝘵𝘦 𝘰𝘯𝘦’𝘴 𝘷𝘪𝘴𝘤𝘦𝘳𝘢𝘭 𝘳𝘦𝘵𝘪𝘤𝘦𝘯𝘤𝘦 𝘵𝘰 𝘳𝘦𝘤𝘰𝘯𝘧𝘪𝘨𝘶𝘳𝘦 𝘢𝘯𝘥 𝘳𝘦𝘷𝘪𝘵𝘢𝘭𝘪𝘴𝘦 𝘥𝘺𝘯𝘢𝘮𝘪𝘤 𝘳𝘦𝘮𝘦𝘮𝘣𝘳𝘢𝘯𝘤𝘦 𝘰𝘧 𝘥𝘪𝘴𝘱𝘭𝘢𝘤𝘦𝘮𝘦𝘯𝘵, 𝘧𝘳𝘢𝘨𝘪𝘭𝘦 𝘵𝘰 𝘧𝘰𝘳𝘨𝘦𝘵𝘧𝘶𝘭𝘯𝘦𝘴𝘴? Grounded in Paul Ricoeur’s theoretical disposition on memory and forgetting, as well as Gilles Deleuze’s conception of displacement, this dissertation critically interrogates contemporary paradigms of memory construction by orchestrating an event of active remembrance. This approach to memory advocates a paradigm shift from object remembrance to active remembrance, informing an ongoing reconstruction of the future through a conscious experiential engagement with the past, thereby subverting the pervasive condition of historical amnesia.
Dissertation (M.Arch.(Architecture))--University of the Free State, 2025
Keywords: South African War; Displacement; Memory; Forgetting; Spectre; War Morphology; Witnessing; Actant